Behavioral Effect of Fructus Psoralea on Ethanol Induced Neurodegeneration of Hippocampus in Wistar Albino Rat - Melani Rajendran3, R. Sivanandan1*, P. Saraswathi2; S. (Recent Research in Science and Technology, 2011)
The behavioral effect of Fructus Psoraleae (FP) was investigated in the rat by using maze apparatus. Ethanol was found to increase the ambulatory, rearing and grooming behaviors in the open-field test. In animal studies, FP increase the number of cholinergic neurons in the basal forebrain which in turn leads to increased hippocampal function, a structure heavily implicated in behavioral activity and memory consolidation. In addition, FP blocked plasma elevated cortisol level, an indicator of the hypothalamic–pituitary–adrenal (HPA) axis. People with extensive hippocampal damage may experience amnesia, learning and memory disabilities. Hence the herb FP may be used as an adjuvant to treat the above neurological disorders.